2007
DOI: 10.1016/j.visres.2007.08.010
|View full text |Cite
|
Sign up to set email alerts
|

HTRA1 variant increases risk to neovascular age-related macular degeneration in Chinese population

Abstract: Age-related macular degeneration (AMD) is a leading cause of irreversible visual impairment in the world. Advanced AMD can be divided into wet AMD (choroidal neovascularization) and dry AMD (geographic atrophy, GA). Drusen is characterized by deposits in the macula without visual loss and is an early AMD sign in the Caucasian population. rs11200638 in the promoter of HTRA1 has recently been shown to increases the risk for wet AMD in both Caucasian and Hong Kong Chinese populations. In order to replicate these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…13,31,35 However, some other studies in Chinese populations revealed much higher ORs. 9,10,36,37 DeWan et al reported that individuals with the risk-associated genotype were estimated to have a likelihood of wet AMD developing around 10 times (OR homo ¼ 11.14 for rs10490924, OR homo ¼ 10.00 for rs11200638) that of individuals with the wild-type genotype. 9 Yang et al found that individuals with the homo risk genotype were around 10fold more likely to have AMD (OR homo ¼ 8.99 for rs10490924, OR homo ¼ 12.93 for rs11200638) than individuals without the risk genotype in a Han Chinese cohort.…”
Section: Discussionmentioning
confidence: 99%
“…13,31,35 However, some other studies in Chinese populations revealed much higher ORs. 9,10,36,37 DeWan et al reported that individuals with the risk-associated genotype were estimated to have a likelihood of wet AMD developing around 10 times (OR homo ¼ 11.14 for rs10490924, OR homo ¼ 10.00 for rs11200638) that of individuals with the wild-type genotype. 9 Yang et al found that individuals with the homo risk genotype were around 10fold more likely to have AMD (OR homo ¼ 8.99 for rs10490924, OR homo ¼ 12.93 for rs11200638) than individuals without the risk genotype in a Han Chinese cohort.…”
Section: Discussionmentioning
confidence: 99%
“…However, two studies have suggested that there may be an association between treatment outcome with ranibizumab therapy and HTRA1 genetic variants for neovascular AMD [27,28]. rs10490924 and rs11200638 were in high linkage disequilibrium (LD) with each other (D´ > 0.98) [12,29]. Therefore, they might not inf luence the treatment outcome independently.…”
Section: Discussionmentioning
confidence: 99%
“…All participants underwent a standard examination protocol, as previously described. 18,23,35 Copyright 2013 The Association for Research in Vision and Ophthalmology, Inc. www.iovs.org j ISSN: 1552-5783…”
Section: Study Populationmentioning
confidence: 99%